Throughcare for Indigenous peoples leaving prison: Practices in two settler colonial states - Tubex, Hilde (European journal of probation, 2021)
The concept of throughcare as a means to prevent recidivism continues to attract considerable attention in Australia over the last couple of years. This is particularly the case for Indigenous peoples, as the transition to life after imprisonment proves to be particularly challenging for them, resulting in high rates of recidivism and ongoing overrepresentation in Australian prisons. In this contribution, we report on research we conducted in two Australian jurisdictions. After identifying the problems in developing effective throughcare strategies for Indigenous peoples leaving prison, we turn to Canada for examples of good practice. Canada was chosen for comparison as it is also a settler colonial state, experiencing similar problems of overrepresentation of their Indigenous population in the prison. After a critical analysis of these practices, we conclude that the reasons for a problematic re-integration of Indigenous peoples are related to a tendency to impose solutions and strategies developed in the white mainstream onto Indigenous communities without acknowledging traditional cultures and structures.